Bidding and performance in repo auctions: evidence from ECB open market operations - Kjell G. Nyborg; Ilya A. Strebulaev; Ulrich Bindseil (European Central Bank (ECB), 2002)
We study bidder bahavior and performance in 53 main refinancing operations (repo auctions) of the European Central Bank (ECB). The data set starts with the first auctions after the ECB changed from fixed rate tenders to variable rate tenders. We find that private information and the winnner's curse are not important in these auctions. The minimum bid rate and the level of secondary market rates play a crucial role in bidder behavior and auction performance. We also document that large bidders do better than small bidders, apparently because they use 'smarter' strategies which involve using more bids and having more kurtosis in their individual bid distribution. The penultimate auction in every reserve maintenance period has less underpricing that the other auctions within the maintenance period. Finally, from the two cases of underbidding covered by the sample period, it appears this was driven by particularly large cutrback by large, rather than small, bidders
Keywords: G21; G12; D44; E43; E50; 330; Efficiency; liquidity; loser's nightmare; Open market operations; repo auctions